Accuracy and acute efficacy of a novel occlusion tool to guide cryoballoon-based pulmonary vein isolation. (14th October 2021) - Rottner, L; Moser, F; Schleberger, R; Weimann, J; Moser, J; Lemoine, M; Muenkler, P; Dinshaw, L; Risius, T; Kirchhof, P; Ouyang, F; Reissmann, B; et al.
Abstract: Background: Cryoballoon (CB)-based pulmonary vein isolation (PVI) currently requires to verify occlusion of each pulmonary vein (PV) using fluoroscopy and dye injection. Objective: The current study evaluated whether the novel CB-occlusion tool integrated into the wide-band dielectric imaging system KODEX-EPD reliably verifies occlusion of PV according to a novel dye-injection based algorithm. Methods: Consecutive patients suffering from symptomatic atrial fibrillation (AF) underwent CB-based PVI using the KODEX-EPD and the novel occlusion-tool (group I). To confirm accurate display of the PVs, selective PV-angiography was performed in the first half of the patients of group I (group Ia) in addition to a three-dimensional left atrial (LA) map using a spiral mapping catheter (Achieve, SMC1, Medtronic, MN, USA). PV-angiographies were waived for the following patients (group Ib). Procedural duration and radiation exposure were compared to a control group of patients undergoing conventional CB-based PVI. Results: CB-based PVI was successful in 50/50 patients of group I (mean age 63±11 years, 18 paroxysmal (36%)) and 25/25 patients of group II (66±10 years, 9 paroxysmal (60%)). Concordance of PV-occlusion as assessed by either PV-occlusion-angiography or KODEX-EPD, was documented in 237/272 (87%) occlusion-analyses among 198 PVs (95% for left superior PV, 93% for left inferior PV, 86% for right inferior PV and 77% for right superior PV). In the final evaluation phase (group Ib) LA fluoroscopy times and dose area products were comparable to the conventional CB-ablation group (10.5±5 vs 8.8±4 minutes (p=0.23) and 403±425 vs 321±202 cGycm 2 (p=0.44), whereas the amount of dye could be significantly reduced (group Ib: 31±10 ml vs group II: 70±20 ml, p<0.0001). Conclusion: The novel KODEX-EPD PV-occlusion tool allows for accurate PV-occlusion assessment in the majority of PVs and a high acute success rate. The system has the potential to reduce dye and radiation exposure. This should be evaluated in controlled clinical trials. Funding Acknowledgement: Type of funding sources: None.